Legal Rationality and Gender Inequality in Judicial Determinations of Marriage Dispensation Due to Pregnancy - Muhammad Fadel Adhyputra; Ziadul Fikri; Hilma Elmumtaziya Adila (Journal of Family Law and Islamic Court, 2026)
The high prevalence of marriage dispensations due to pregnancy has the potential to generate gender injustice against girls. This study aims to examine the construction of judges' legal rationality in granting marriage dispensations and to identify the forms of gender injustice manifested therein. This study employs a qualitative socio-legal method with a gender studies approach. The analysis is based on documents of marriage dispensation rulings at the Bantul Religious Court before and after the enactment of Law Number 16 of 2019, and is complemented by a comparison with rejection decisions at the Painan Religious Court. The analysis draws on Max Weber's theory of legal rationality and Mansour Fakih's concept of gender injustice. The findings show that procedural modernization has not been accompanied by changes in the substance of judicial reasoning, where pregnancy continues to be positioned as an emergency condition that legitimizes child marriage. In contrast, judges at the Painan Religious Court position pregnancy as an indicator of fundamental unpreparedness for marriage, thereby rejecting dispensation applications; however, their reasoning remains laden with moral stigma that disproportionately burdens girls. This practice perpetuates subordination, marginalization, stereotypes, symbolic violence, and the double burden on girls, indicating the lack of integration of a gender perspective in judicial considerations.